ARUS KAS ANALISIS LAPORAN ARUS KAS OPERASI, INVESTASI, DAN PENDANAAN STUDI KASUS PERUSAHAAN DI BURSA EFEK INDONESIA - Supriono Supriono (Jurnal Ekonomi dan Teknik Informatika, 2023)
Economic relations between countries are influenced by rapidly developing technology, this also affects the transportation and logistics sector. Current technological advances also affect e-commerce activities, namely buying and selling transactions using electronic media. The transportation and logistics sector has an important role in supporting these activities. The purpose of this study is to analyze the company's cash flow statements at transportation and logistics companies listed on the Indonesia Stock Exchange, and to find out the cash flow patterns during 2016-2019. Cash flows are activities of cash inflows and cash outflows of cash and cash equivalents. Cash flow information is useful for measuring the performance of entities in obtaining cash and cash equivalents as well as for measuring the needs of entities to use cash flows. The analysis technique used in this study is a horizontal analysis technique, namely comparing cash flow statements with previous periods. The sampling method uses purposive sampling, which is a sampling technique by determining certain criteria. There are 20 companies that meet the requirements The results of this study are that there is a decrease and increase in every operating activity, investment activity, and funding activity. The cash flow pattern for the four years has two distinct patterns. In 2016 and 2019 the company used the excess operating cash flow and funding to invest, purchase fixed assets or expand the business. Whereas in 2017 and 2018 excess operating cash flow was used to purchase fixed assets and pay long-term debt to creditors or make prive payments or cash dividends to owners or investors